Analysis of Technology Acceptance of Enterprise Resource Planning (ERP) System in The Regional Office of PT. XYZ Throughout Indonesia - Baiq Findiarin Billyan; Mohammad Isa Irawan (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2021)
The companies that started to renew their system using ERP-based systems, since 2000 the percentage of success reached 75%, and 25% is a failure. There are several issues such as the quality of human resources, not user-friendly system, incorrect format for data recording, system errors, unstable connections, the long-time process in the system, etc. Related to the issue, the ERP SAP technology provider provides local support to help end-users use the system for daily work. In this study, to analyze the factors of acceptance technology of ERP system, we use the UTAUT2 method, and for analyzing those hypotheses, we use the PLS-SEM metho